Kebijakan Partisipatif Pemerintah dalam Rangka memenuhi Visi Terwujudnya Kabupaten Pasuruan yang Sejahtera, Maslahat dan Berdaya Saing - Khoirul Huda (Universitas Yudharta Pasuruan, 2020)
One of the objectives of the state being established is to protect life and advance the welfare of the nation, so the government is obliged to help fulfill the basic rights of society. The high mortality rate for mothers and newborns is not just a matter of fate, but something that is done by humans. The maternal and newborn mortality rate in Indonesia is the highest compared to other countries in ASEAN. In response to this, the Pasuruan Regency Government responded by making a policy in the form of the establishment of the Penakib Forum which has a vision to make Pasuruan district a safe, safe and pleasant place for every pregnant woman. and newborns. This forum consists of all cross-sectoral components, namely consisting of the health office, referral hospitals, puskesmas, village midwives, health cadres, and community organizations in Pasuruan Regency. This vision is in accordance with the regional medium-term development plan (RPJMD) for 2018 - 2023 which carries the vision